Vaping additives cannabinoid oil and vitamin E acetate adhere to and damage the human airway epithelium. Issue 5 (30th November 2022) - Reidel, Boris; Abdelwahab, Sabri; Wrennall, Joe Alexander; Clapp, Phillip W.; Beers, Jessica L.; Jackson, Klarissa D.; Tarran, Robert; Kesimer, Mehmet
Abstract: E‐cigarette, or vaping product use‐associated lung injury (EVALI), is a severe respiratory disorder that caused a sudden outbreak of hospitalized young people in 2019. Using cannabis oil containing vaping products, including vitamin E acetate contaminants, was found to be strongly associated with EVALI. However, the underlying tissue impacts of the condition are still largely unknown. Here, we focused on the vehicle cannabinoid oil (CBD oil) and contaminant vitamin E acetate (VEA) effects on airway epithelial cells. Primary human bronchial epithelial (HBE) cultures were exposed to e‐liquid aerosols that contained CBD oil and VEA in combination or the common e‐liquid components PG/VG with and without nicotine. Cell viability analysis indicated dramatically increased cell death counts after 3 days of CBD exposure, and this effect was even higher after CBD + VEA exposure. Microscopic examination of the cultures revealed cannabinoid and VEA depositions on the epithelial surfaces and cannabinoid accumulation in exposed cells, followed by cell death. These observations were supported by proteomic analysis of the cell secretions that exhibited increases in known markers of airway epithelial toxicity, such as xenobiotic enzymes, factors related to oxidative stress response, and cell death indicators. Overall, our study provides insights into the association between cannabinoid oil and vitamin E acetate vaping and lung injury. Collectively, our results suggest that the adherent accumulation of CBD oil on airway surfaces and the cellular uptake of both CBD oil‐ and VEA‐containing condensates cause elevated metabolic stress, leading to increased cell death rates in human airway epithelial cultures. Abstract : E‐cigarette, or vaping product use‐associated lung injury (EVALI), is a severe respiratory disorder that caused a sudden outbreak of hospitalized young people in 2019. Despite an association with cannabinoid containing vaping products, the underlying tissue impacts of the condition remained largely unknown. Our study reveals that the adherent accumulation of CBD oil on airway surfaces and the cellular uptake of CBD oil‐ and VEA‐containing condensates cause elevated metabolic stress, leading to increased cell death rates in human airway epithelial cultures.